Uji Daya Hambat Ekstrak Daun Jamblang (Syzygium Cumini (L.) Skeels) Terhadap Pertumbuhan Bakteri Streptococcus Pyogenes dan Proteus Mirabilis - Venny Patricia; Wawan Sofwan Zaini; Ahmad Yani; Siti Atikah (Jaringan Laboratorium Medis, 2021)
Infectious diseases are a problem for public health and can increase patient morbidity and mortality. Bacteria that cause infectious diseases include Streptococcus pyogenes and Proteus mirabilis. Inappropriate use of antibiotics can cause resistance problems and the effects of undesirable drugs. Jamblang (Syzygium cumini) leaf extract can be used as a natural antibacterial drug. There is a study showing the content of active compounds in the leaves of Jamblang are Flavonoids, tannins, alkaloids, and saponins are components of chemical compounds that are suspected as antibacterial. This study aims to determine the antibacterial activity of Jamblang leaf extract against Streptococcus pyogenes and Proteus mirabilis bacteria. The method used is the Minimum Inhibitory Concentration method using well diffusion. The study used Jamblang leaf extract with various concentrations of 10%, 20%, 30%, and 40%, the test bacteria used were Streptococcus pyogenes and Proteus mirabilis, using positive control of chloramphenicol, and negative control of 10% DMSO. The results showed that Jamblang leaf extract can inhibit the growth of Streptococcus pyogenes and Proteus mirabilis bacteria in all concentrations. In the Kruskall Wallis Non-Parametric statistical test the two bacteria obtained P 0.05.In Streptococcus pyogenes bacteria the value of P = 0.031, and Proteus mirabilis bacteria the value of P = 0.015. These results indicate a real difference in this study.